POTENTIAL RISKS OF SLEEP DISORDERS IN CHILDREN OF THE KHARKIV OBLAST DURING THE MILITARY CONFLICT: SURVEY RESULTS - Riga, Olena; Onikiienko, Oleksandr; Sych, Diana; Tkachenko, Olha; Tsymbal, Valentyn; Sanina, Iryna (Eastern Ukrainian Medical Journal, 2024)
Introduction. Problems of sleep disorders in children are not given much attention. Since the beginning of military activities on the territory of Ukraine, sleep quality has been affected by different factors. Materials and Methods. We surveyed 232 healthy children aged 11–18 years who were residents of the Kharkiv Oblast and determined potential factors of sleep disorders depending on age, gender, and environmental factors using an original 20-question questionnaire in April 2023. Descriptive and logistic regression analyses were used. Results. We registered age-dependent sleep behaviour disorders, which increased with age. 99 (42.7 %) children were found to go to bed after 24:00, while 122 (52.6 %) children slept less than 7–8 hours a day. The use of gadgets before going to bed for more than 2 hours was characteristic of children older than 13 years, and 66 (28.4 %) children used them for more than 3 hours. 32 (13.7 %) children associated the use of gadgets with poor sleep, 50 (21.5 %) children – with headaches, 93 (40.0 %) children – with morning weakness, and 148 (63.7 %) children – with doing homework. Forcibly relocated children did not go to bed when they felt they wanted to sleep 1.6 times more often; they had a sleep duration of less than 7 hours 5 times more often and noted daytime fatigue 1.4 times more often. Staying in Kharkiv and the region during the hostilities led to sleep behaviour disorders, namely, the inability to fall asleep and wake up at the same time, 1.2 times more frequently. Conclusions. A significant contribution to sleep behaviour disorder in children is made by the use of gadgets before going to bed and doing school homework, forced relocation and living in the Kharkiv Oblast during the military conflict.